An experimental and theoretical investigation of the photocatalytic degradation of meta-cresol in TiO2 suspensions: a model for the product distribution - Hatipoglu, A; San, N; Çinar, Z (ELSEVIER SCIENCE SA, 2004)
The kinetics of the photocatalytic degradation of meta-cresol (m-CR) in the presence of TiO2 has been investigated experimentally and theoretically. The effects of the catalyst loading and the initial concentration of m-CR on the degradation rate have been examined. A pseudo-first order kinetic model has been used to describe the results. A linear dependence of the rate constant upon the reciprocal of the initial m-CR concentration has been obtained. With the intention of predicting the primary intermediates and the product distribution, geometry optimizations of the reactants, the product radicals and the transition state complexes have been performed with the semiempirical PM3 method. The molecular orbital calculations have been carried out by an SCF method using RHF or UHF formalisms. Based on the results of the quantum mechanical calculations, the rate constants of the six possible reaction paths have been calculated by means of the transition state theory. Three predictors have been determined for the prediction of the most probable transition state and the reaction path. Branching ratio for each of the reaction paths has been calculated and the most probable intermediate has been determined to be 1,6-dihydroxy-3-methyl-cyclohexadienyl radical which then forms 3-methylcatechol. The results show that m-methylphenoxyl and m-hydroxybenzyl radicals which cause the formation of polyaromatics are not produced in the photodegradation of m-CR. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: photocatalytic degradation; photodegradation; hydroxyl radicals; m-cresol; PM3 method; TITANIUM-DIOXIDE; AQUEOUS SUSPENSIONS; SEMIEMPIRICAL METHODS; PHENOL; OXIDATION; 2-CHLOROPHENOL; HYDROXYLATION; CHLOROPHENOLS; OPTIMIZATION; Chemistry